Agonística expressa em circulação: o Papa Francisco como articulador de sentidos - Milani, Tatiane (Universidade do Vale do Rio dos Sinos, 2019)
The research object explored in this dissertation is inserted in a context of transformations not only from the Communication, but from a society, general speaking, that transforms from new interactive models, as well as the complexity of such relations. The research aims at Pope Francis, in which the empirical is constituted from sayings and ways of acting of the pontiff during the first five years of the pontificate (2013-2018). The entry of a religious figure for the research in the communication field is proposed due to the complex movement of interactional procedurals perceived events in this period, reflecting the accelerated production of meanings in interactions between the Catholic Church, the media and society. Before inserting the object into the circulation, the central objective of the research is to understand the specifics and interactive logic in that interactional clashes occur, and how Pope Francis develops tactics to articulate this dispute presented in the agonistic. The corpus of the research consists of an interactional element starter circulation - in our work the collective on the plane in 2013, followed by two episodes that are triggered in this collective: Episode 1 – sentence about homosexuals and Episode 2 - second wedding union, and finally, an episode that is not directly related to the collective, but is constituted from the interactional logics of airplane that is the episode 3 – Wedding carried out in flight. The episodes are selected in the research because they deal with social conflicts enhanced by circulation, which demand a stance from Pope Francis who tries to orchestrate the debates, just as there is the positioning of society that is embedded in such issues. For the analysis of the materialities, we observe the specificities of the triggering element of the circulation and make a relation with the systematization of the episodes, which within their particularities constitute circuits. From the observation of the articulating traits in each episode, we delimit the research case, formulated following discursive marks and operations present in the interactions of the participants in each circumstance. Therefore, in this work we are interested in looking at the following axes: the logics and strategies in the context of airplane talk; the circuits; the way the pope tries to guide the debate; the agonistic, and the images in dispute through the senses in tension. Theoretical drives proposed by empirical object depart from caring how the senses are perceived (VERON, 1980; DELLEUZE, 1974) from interactions (BRAGA, 2012; AUSTIN 1990), and what we perceive as communicative action from the sayings of the subjects, in view of proceduralities. Then we enter in the circulation theme (VERON 2013; FAUSTO NETO, 2013; FERREIRA, 2006; 2007). This is approached from the structure of the communicational model, making the journey in the sphere of grammars of production and recognition that are the process that results in the senses in dispute. Then, we work with the notion of circuits as a complex place of interactions, and to close the circulation item we approach the image disputes (ROSA, 2012; 2014; 2015) that also occur in the face of the vast production of meanings. The theoretical chapter ends up based on the context of the dispositional arrangements (BRAGA 2011; 2017; 2018) giving centrality to the agonist in play, being this the communicational process that occurs.
Keywords: Papa Francisco; Circulação midiática; Dispositivo interacional; Imagem; Agonística; Pope Francis; Media circulation; Interactive device; Image; Agonistic; ACCNPQ::Ciências Sociais Aplicadas::Comunicação